Magnitude and determinants of abnormal uterine bleeding among reproductive-age women in Kombolcha Rejiopolitan Administrative Town, Northeast Ethiopia: a FIGO-based study (2023) - Seid, Abubeker; Bulto, Gizachew Abdissa; Yesuf, Adem; Yimer, Ali; Ahmed, Hassen; Muse, Tsegaye Benti (Frontiers in Reproductive Health, 2025)
BackgroundAbnormal uterine bleeding (AUB) is a common reason for women to seek healthcare, affecting their health, quality of life, productivity, and increasing the risk of complications. While menstrual disorders have been studied in Ethiopia, the prevalence and determinants of AUB among reproductive-age women remain poorly understood due to the use of outdated terminology and a lack of standardized approaches, which hinder accurate assessment and comparison with international findings. This study aims to address this gap by assessing the magnitude and determinants of AUB among reproductive-age women in Kombolcha town, Ethiopia, using the 2018 FIGO criteria.MethodsA community-based cross-sectional study was conducted among 608 reproductive-age women in Kombolcha town from April 20 to May 20, 2023, using systematic random sampling. Data were collected using interviewer-administered structured questionnaires. The data were entered into EPI Data version 4.6 and analyzed using SPSS version 26. All predictor variables with a p-value <0.25 in bivariable analysis were included in multivariable logistic regression. Variables with a p-value <0.05 in the multivariable analysis were considered statistically significant predictors of abnormal uterine bleeding.ResultThis study found that 36.5% of 591 reproductive-age women experienced abnormal uterine bleeding (AUB). Several factors were significantly associated with AUB: Women in late reproductive age (41–49 years) had 4.2 times higher odds of experiencing AUB compared to those in mid-reproductive age (AOR = 4.181, 95% CI: 2.199–7.948). Hypertensive women were 3.71 times more likely to experience AUB (AOR = 3.706, 95% CI: 1.106–12.417). Women with a history of abortion had 2.3 times higher odds of AUB (AOR = 2.345, 95% CI: 1.069–5.147). A history of diagnosed anemia and late menarche (≥15 years) were also significantly associated with increased AUB risk (AOR = 2.939, 95% CI: 1.437–6.010; AOR = 3.824, 95% CI: 2.199–7.948).ConclusionThis study highlights the significant burden of AUB, with 36.5% of women affected. Healthcare providers should educate patients about lifestyle changes, treatment options, and when to seek emergency care for AUB to improve health outcomes.